2018
DOI: 10.1038/s41394-018-0102-7
|View full text |Cite
|
Sign up to set email alerts
|

Fractures and musculoskeletal ailments in persons 20+ years after a traumatic spinal cord injury in Norway

Abstract: Around half of the 165 participants reported to have suffered a fracture and over 100 to experience musculoskeletal ailment 20 years after injury. We suggest that prevention strategies and symptom management must be embedded in follow-up visits after SCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…Twenty-seven percentage of our study group reported fractures at baseline with a 5% fracture rate during the 1-year follow-up. Higher numbers of years since injury were associated with a higher risk of fracture post injury at baseline (see Table 4b), which is similar to previous reports [6, 25–30]. Two out of five individuals in the prospective fall-related fracture group had experienced a previous fracture (see Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…Twenty-seven percentage of our study group reported fractures at baseline with a 5% fracture rate during the 1-year follow-up. Higher numbers of years since injury were associated with a higher risk of fracture post injury at baseline (see Table 4b), which is similar to previous reports [6, 25–30]. Two out of five individuals in the prospective fall-related fracture group had experienced a previous fracture (see Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…Our protocol was based on data from four different sources: (a) medical records, (b) clinical examinations, (c) interviews including semistructured and standardized questionnaires, and (d) either clinic attendance or visits to the participant's home. Information extracted from each patient's medical record was to include: demographic data (gender, age at [7] International SCI Skin and Thermoregulation Function Basic Data Set Version 1.0 English [8] International SCI Bowel Function Basic Data Set Version 1.1 English [9] International SCI Pain Basic Data Set Version 2.0 English [10] International SCI Lower Urinary Tract Basic Data Set Version 1.0 English [11] A self-made questionnaire [6] International SCI Core Data Set Version 1.1 English [12] Quality of life basic data set (Version 1.0), English [13] International Standards for Neurological Classification of Spinal Cord Injury, including AIS [5] SCI spinal cord injury; AIS American Spinal Cord Injury Association (ASIA) Impairment Scale injury, and current employment status), date of admission and discharge from the hospital, past medical history, injury-related information, type of injury, neurological level of injury (NLI), and American Spinal Cord Injury Association (ASIA) Impairment Scale (AIS) classification [5], associate injuries, injury-related complications, and mortality. The clinical examination was to include NLI and AIS.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical examination was to include NLI and AIS. An interview with fixed questions was especially developed based on previous research [6] and clinical experience. The interview included the following topics: complications, sequela, and ailments, mobility and sports aids/equipment, transport, home adjustments, and the use of personal assistance.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately one third of these cases involve incomplete lesions, allowing for some muscle activity below the affected area [3]. In comparison to complete injuries, incomplete SCIs tend to be less severe, although patients still encounter limitations in various aspects of their lives, with an increased vulnerability to falls [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%